Genotype- and sex-specific changes in vital parameters during isoflurane anesthesia in a mouse model of Alzheimer’s disease - Bratke, Sebastian; Schmid, Sebastian; Ulm, Bernhard; Jungwirth, Bettina; Blobner, Manfred; Borgstedt, Laura (Frontiers in Medicine, 2024)
The prevalence of neurodegenerative diseases is increasing as is life expectancy with Alzheimer's disease accounting for two-thirds of dementia cases globally. Whether general anesthesia and surgery worsen cognitive decline is still a matter of debate and most likely depending on the interplay of various influencing factors. In order to account for this complexity, Alzheimer's disease animal models have been developed. The Tg2576 model of Alzheimer's disease is a well-established mouse model exhibiting amyloidopathy and age-dependent sex-specific differences in Alzheimer's disease symptomology. Yet, data on anesthesia in this mouse model is scarce and a systematic comparison of vital parameters during anesthesia with wild-type animals is missing. In order to investigate the safety of general anesthesia and changes in vital parameters during general anesthesia in Tg2576 mice, we did a secondary analysis of vital parameters collected during general anesthesia in aged Tg2576 mice.After governmental approval (General Administration of the Free State of Bavaria, file number: 55.2-1-54-2532-149-11) 60 mice at 10-12 months of age were exposed to isoflurane (1.6 Vol%) for 120 minutes, data of 58 mice was analyzed. During general anesthesia, heart rate, respiratory rate, temperature, isoflurane concentration and fraction of inspired oxygen were monitored and collected. Data were analyzed using univariate and multivariate linear mixed regression models. Genotype-and sex-specific changes in vital parameters during isoflurane anesthesia in a mouse model of Alzheimer's diseaseDuring general anesthesia, heart rate decreased in a sex-specific manner. Respiratory rate decreased and body temperature increased dependent on genotype. However, the changes were limited and all vital parameters stayed within physiological limits.Isoflurane anesthesia in the Tg2576 mouse model is safe and does not seem to influence experimental results by interacting with vital parameters. The present study provides information on appropriate anesthesia in order to advance research on anesthesia and AD and could contribute to improving laboratory animal welfare.